Educating Generation Z: Integrating Digital Platforms into Learning: Mendidik Generasi Z: Mengintegrasikan Platform Digital dalam Pembelajaran - Chambia, Much. Ahmad Syehra; Haryanto, Budi (Indonesian Journal of Education Methods Development, 2025)
General Background : This study explores how teachers can leverage digital platforms to create relevant and engaging learning in the digital era. Specific Background : The research focuses on the integration of digital tools and platforms, which have become a core part of modern life. Knowledge Gap : While digital tools are widespread, there is a need to understand how teachers can effectively use these platforms to meet the unique learning needs of students in a digital-first environment. Aims : This study employs a qualitative literature review and content analysis to identify patterns and draw conclusions on the effective use of digital platforms in education. Results : The findings indicate that digitalization has significantly transformed education through various platforms that make learning more engaging and accessible for students. Novelty : This research provides a structured analysis of how existing digital platforms can be utilized to transform teaching methods, offering a new framework for creating engaging and relevant learning experiences. Implications : The study implies that by effectively integrating digital platforms, teachers can better cater to the needs of modern students, fostering a more interactive and creative learning environment. Highlights : The use of digital platforms transforms learning, making it more engaging and accessible for students. The research utilizes a qualitative literature review and content analysis to find patterns and draw conclusions. The main goal is to explore how teachers can use digital platforms to create relevant and engaging learning experiences in the digital era. Keywords : Digital Platforms, Education, Teacher Strategies, Learning, Digital Era